2020
DOI: 10.1001/jamanetworkopen.2020.4813
|View full text |Cite
|
Sign up to set email alerts
|

Association of Electronic Nicotine Delivery System Use With Cigarette Smoking Relapse Among Former Smokers in the United States

Abstract: IMPORTANCE Relapse to smoking among former smokers is a serious clinical concern, and use of electronic nicotine delivery systems (ENDS) has been proposed as a new risk factor for relapse. Understanding the specificity of this risk can help guide clinical practice and lead to improved health outcomes. OBJECTIVE To assess the associations of ENDS use with cigarette smoking relapse among adult former cigarette smokers. DESIGN, SETTING, AND PARTICIPANTS This cohort study examined data from the Population Assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 30 publications
0
53
0
2
Order By: Relevance
“…All studies estimated the risk of relapse adjusted for covariates, including age, gender, income, and educational level. Brose et al 22 included further information on nicotine replacement therapy and cessation duration among former smokers, while Everard et al 18 and Gomajee et al 16 included the greatest number of covariables in the model.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All studies estimated the risk of relapse adjusted for covariates, including age, gender, income, and educational level. Brose et al 22 included further information on nicotine replacement therapy and cessation duration among former smokers, while Everard et al 18 and Gomajee et al 16 included the greatest number of covariables in the model.…”
Section: Resultsmentioning
confidence: 99%
“…According to the risk of bias assessment, two studies were classified as low risk 16 , 19 , two moderate 18 , 22 and two high risk 20 , 21 . The risk of bias was mainly affected in domains related to the adjustment of confounding variables, and the loss of follow-up or failure to consider it in the analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, there is limited evidence about ENDS effectiveness as a cessation or harm reduction tool for adults (e.g., Hajek et al, 2019), especially in real-world settings. Real-world perspective studies with nationwide samples in the US (e.g., the Population Assessment of Tobacco and Health, PATH) have shown that dual-use remains the most common trajectory of ENDS use in the society (Watkins et al, 2018) and that former cigarette smokers using ENDS are more likely to relapse to cigarette smoking compared to those who did not use ENDS (Dai & Leventhal, 2019b;Everard et al, 2020). Therefore, until additional policies that can tailor ENDS products for smoking cessation are available, the combination of a highly addictive ENDS that is marketed and popular among youth is not in the best interest of public health.…”
Section: Discussionmentioning
confidence: 99%